**Unformatted text preview: **m x m =-mx m-1 x m x m =-mx m-1 x 2 m =-mx m-1-2 m = nx-m-1 = nx n-1 . We will later see why the other cases of the power rule work, but from now on we will use the power rule whenever n is any real number. Let’s note here a simple case in which the power rule applies, or almost applies, but is not really needed. Suppose that f ( x ) = 1; remember that this “1” is a function, not “merely” a number, and that f ( x ) = 1 has a graph that is a horizontal line, with slope zero everywhere. So we know that f ± ( x ) = 0....

View
Full Document

- Fall '07
- JonathanRogawski
- Math, Calculus, Power Rule, lim, Negative and non-negative numbers